Efficacy of Anthem Maxx, Solstice, Cadet, Roundup PowerMax, and Competitive Standards in Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Control of Palmer amaranth and green foxtail was generally best when herbicides were applied as sequential treatments of preemergence (PRE) followed by late postemergence (LPOST) or as postemergence (POST) alone. Velvetleaf and puncturevine control was 95 and 93% or more, respectively, regardless of herbicide or application timing. Corn receiving herbicide treatments yielded 42 to 72 bu/a more grain than non-treated corn.
Keywords: irrigated corn; weed control; postemergence applications; Palmer amaranth; puncturevine; velvetleaf; green foxtail; Anthem Maxx; Pyroxasulfone; Fluthiacet; Solstice; Mesotrione; Cadet; Roundup Powermax; Glyphosate